(untitled) (Modern information system and technologies, 2018)
This article discusses the development of a mobile application for paying of taxes, simplification and automation of payment, as well as push notices for reminders of deadlines. Keywords: mobile application, FOP taxes, JS language, push notifications, AngularJs, WebStorm